2016
DOI: 10.3390/polym8120418
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Layers on the Surface of Polyester-Based Materials for Improvement of Their Biointeractions and Controlled Release of Proteins

Abstract: Abstract:The modification of bioresorbable polyester surfaces in order to alter their biointeractions presents an important problem in biomedical polymer science. In this study, the covalent modification of the surface of poly(lactic acid)-based (PLA-based) films with poly(acryl amide) and sodium alginate hydrogels was performed to change the non-specific polyester interaction with proteins and cells, as well as to make possible the covalent attachment of low-molecular weight ligands and to control protein rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Specifically, the MTT assay revealed that the RGRs of PLA, PLA/MWCNT-Ag 0.1 , and PLA/MWCNT-Ag 0.2 after 72 h of incubation were 258.76%, 176.29%, and 126.39%, respectively. These specimens also had a cytotoxicity score of grade 0 (ISO 10993-5) [ 24 , 25 ], indicating no cytotoxicity. L929 fibroblasts exhibited a normal proliferation rate after incubation, with extracts of the PLA with low MWCNT-Ag content (0.1–0.2 phr).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the MTT assay revealed that the RGRs of PLA, PLA/MWCNT-Ag 0.1 , and PLA/MWCNT-Ag 0.2 after 72 h of incubation were 258.76%, 176.29%, and 126.39%, respectively. These specimens also had a cytotoxicity score of grade 0 (ISO 10993-5) [ 24 , 25 ], indicating no cytotoxicity. L929 fibroblasts exhibited a normal proliferation rate after incubation, with extracts of the PLA with low MWCNT-Ag content (0.1–0.2 phr).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate and compare the effect of polyester modification with polyelectrolyte layers on the surface hydrophobicity, the contact angles of corresponding films (PLA, PCL, PLA-PLys, PCL-PLys, PLA-PLys-Hep, PCL-PLys-Hep, PLA-(PLys-Hep) 2 , PCL-(PLys-Hep) 2 ) were measured. The films were prepared and characterized as described before [33]. Briefly, a 1.5 µL water drop was placed on the film surface, and the average static contact angle was determined using the drop analysis plugin (Biomedical Imaging Group, Lausanne, Switzerland) for ImageJ software during the first 30 s following the drop deposition.…”
Section: Evaluation Of Particles Physicochemical Properties Drug Entrapment Efficiency and Release Kineticsmentioning
confidence: 99%
“…When dealing with polyesters’ biofunctionalization, one will face their relative hydrophobicity and lack of reactive groups for biomolecule attachment [27,28,29]. Only the terminal hydroxyl and carboxylic groups are available for modification without chain cleavage.…”
Section: Introductionmentioning
confidence: 99%